Determination of optimum moisture content for aggregation of S300 kaolin - Fang, Liew Siew (2015)
Soil aggregation is the behaviour of groups of soil particles that bind each other together. Generally, soil aggregation is frequently found in agriculture industry as the tillage and re-compaction of soil particles. The best soil aggregation requires optimum moisture content as water is crucial to soil for achieving aggregation. This research was done to determine the soil properties of S300 kaolin and to study the aggregated pore structures of S300 kaolin samples. Besides that, this research is conducted to determine the optimum moisture content for S300 kaolin aggregation. S300 kaolin was used in this research as it is commercially available and easily obtainable. Furthermore, S300 kaolin clay is suitable for this research as double porosity characteristics is able to be created and seen in kaolin. There are five kaolin samples, each with different moisture content, 26%, 28%, 30%, 32%, and 34%. Common soil properties experiments are done to S300 kaolin and Environmental Scanning Electron Microscope (ESEM) machine was used too in order to analyze the double porosity feature in S300 kaolin aggregated samples. This research proves that S300 kaolin clay was purely fine-grained inorganic clay soil with low to medium plasticity, classified using Unified Soil Classification System (USCS). The specific gravity of kaolin is within the range of the standard clay and the permeability also satisfied the standard of clay. Apart from that, results from ESEM machine are shown to prove that 30% of moisture content was the optimum moisture content for aggregation of S300 kaolin. The soil structure for aggregation of S300 kaolin clay shows double porosity characteristics at 30% of moisture content. The results and analysis of this research will contribute to future research of groundwater contamination problems